Modifications in Lignin during Oxygen Delignification and its Impact on Pulp Fibers of Eucalyptus tereticornis - Bhatnagar, Anju (Indian Forester, 2016)
The objective of the paper is to study the structure of lignin of Eucalyptus tereticornis kraft pulp during oxygen delignification for evaluation of pulp fibers properties and dissolution behavior of lignin. Eucalyptus tereticornis kraft pulp of kappa number 44.91 and 26.46 were delignified by 8 Kg/cm2 oxygen pressure, by varying reaction temperature (90-120Â°C) and charge of sodium hydroxide( 0-5%). Oxygen bleachability was found to be correlated to the incoming kappa number and charge of sodium hydroxide employed. The residual lignin in the oxygen delignified kraft pulp of kappa number 21.32, 12.84, 13.03 and 12.18 samples was isolated and characterized by elemental composition, functional groups analysis and IR spectroscopy. Elemental composition and empirical formula of lignin derived from these values indicated that oxygen treated pulp lignins have lower amount of carbon and higher amount of hydrogen and oxygen as compared to kraft pulp lignins. Methoxyl, hydroxyl and phenolic contents were decreases on bleaching. IR spectroscopic studies were also indicated the decrease in methoxyl content. Oxygen delignified pulps were enriched with a-Carbonyl groups and carboxyl groups. The physical strength properties of oxygen delignifed pulps were assessed in terms of tensile strength, tear strength and burst strength. The results are discussed in the paper at adequate length.